A study to investigate the relationship between the characteristics of salespeople and the buying behaviour of the Silver Market Consumers. - Cheo, Ting Ting. (2010)
The ageing population trend in recent years has brought about the rise of the silver market all over the world. This research study aims to find out which characteristics of a salesperson would appeal to the Silver Market Consumers (SMC) in Singapore. For the purpose of this study, we have chosen to focus on the retail healthcare products industry. The three main objectives of this study are: To determine the characteristics of salespeople that lead to positive affect of the SMC in the retail healthcare products industry, to determine how affect influences their buying behaviour, and to provide retailers in this industry with relevant information to assist them in their selection and training of salespeople. Data was collected through self-administered questionnaires gathered from 100 respondents aged 55 and above.